2002
DOI: 10.1097/00001888-200208000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Resident Physicians to Provide Exercise Counseling

Abstract: Resident physicians' perceptions of exercise counseling as a priority, confidence in counseling skills, and postgraduate year of training are important predictors of their providing exercise counseling. These factors should be addressed in future educational programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 7 publications
3
38
1
Order By: Relevance
“…9,10 We placed these recommendations in the context of competency-based residency training per the Accreditation Council of Graduate Medical Education (ACGME) and the American Board of Internal Medicine (ABIM), looking at curriculum development in physical activity and nutrition counseling as it relates to the six core competencies. 11 Literature review confirmed low counseling rates of patients at risk for CVD in our program 6 and in other residency programs [12][13][14] and documented studies on reported barriers to physician counseling. [15][16][17] We then conducted a targeted needs assessment defined in step two of Kern's six-step approach as "assessing the needs of one's targeted group of learners and their medical institution/ learning environment, which may be different from the needs of learners and medical institutions in general."…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…9,10 We placed these recommendations in the context of competency-based residency training per the Accreditation Council of Graduate Medical Education (ACGME) and the American Board of Internal Medicine (ABIM), looking at curriculum development in physical activity and nutrition counseling as it relates to the six core competencies. 11 Literature review confirmed low counseling rates of patients at risk for CVD in our program 6 and in other residency programs [12][13][14] and documented studies on reported barriers to physician counseling. [15][16][17] We then conducted a targeted needs assessment defined in step two of Kern's six-step approach as "assessing the needs of one's targeted group of learners and their medical institution/ learning environment, which may be different from the needs of learners and medical institutions in general."…”
Section: Methodssupporting
confidence: 54%
“…To assess professional attitudes toward counseling, we developed open and closed ended questions regarding potential barriers based on published barriers to counseling. [12][13][14][15][16][17] We then developed questions on resident practices in physical activity and nutrition counseling. The self-administered KAP survey used multiple choice questions for the knowledge and practices portions and 5-point Likert scale questions for the attitudes portion.…”
Section: Kap Questionnairementioning
confidence: 99%
“…[1][2][3][4] The reasons for these disparities are complex and include patient, provider and health system-level factors. 5 For example, lower utilization of health-promoting behaviors (e.g., healthy diet and exercise) among African-Americans 6 can contribute to diabetes disparities and reflect patientlevel factors such as cultural beliefs or access to safe recreational facilities, [7][8] physician-level factors such as skill at lifestyle counseling, 9 and health system-level factors such as the availability of nutritionists and regional practice variation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has found issues such as lack of time, inadequate training or lack of confidence in weight management to be reasons for the incomplete documentation of weight management plans in primary care settings 10. A significant role is also played by whether exercise counselling skills are perceived as a priority by the clinician and whether these skills were taught to the respective practitioner during his/her postgraduate year of training 11. Exposure to apt levels of training in advocating weight management to all patients and undertaking exercise/physical activity counselling during postgraduate education of physicians has been found to be significant in improving practitioner skills in real‐world practice and provides the required level of confidence in doing so on a regular basis 10, 11.…”
Section: Discussionmentioning
confidence: 99%
“…A significant role is also played by whether exercise counselling skills are perceived as a priority by the clinician and whether these skills were taught to the respective practitioner during his/her postgraduate year of training 11. Exposure to apt levels of training in advocating weight management to all patients and undertaking exercise/physical activity counselling during postgraduate education of physicians has been found to be significant in improving practitioner skills in real‐world practice and provides the required level of confidence in doing so on a regular basis 10, 11. Although most general practitioners would acknowledge the importance of weight management both in terms of BMI recording and undertaking preventive health counselling, evidence among general practitioners does reveal differences between self‐reports of current practice and perceived desirable practice by general practitioners 12.…”
Section: Discussionmentioning
confidence: 99%